MODERN APPROACHES TO THE TREATMENT OF EPILEPSY – PHARMACOLOGICAL, SURGICAL, AND NEUROMODULATION STRATEGIES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The management of epilepsy has evolved substantially over the past decades, with the development of new antiepileptic drugs and advanced surgical and neuromodulatory techniques. The primary therapeutic goal is complete seizure control without significant side effects. This article discusses current treatment strategies, including pharmacotherapy, epilepsy surgery, and neuromodulation.